Ketogenic diet and skeletal muscle hypertrophy: a frenemy relationship? - Paoli, A.; Cancellara, P.; Pompei, P.; Moro, T. (Journal of Human Kinetics, 2019)
Ketogenic diet (KD) is a nutritional regimen characterized by a high-fat and an adequate protein content and a very low carbohydrate level (less than 20 g per day or 5% of total daily energy intake). The insufficient level of carbohydrates forces the body to primarily use fat instead of sugar as a fuel source. Due to its characteristic, KD has often been used to treat metabolic disorders, obesity, cardiovascular disease, and type 2 diabetes. Skeletal muscle constitutes 40% of total body mass and is one of the major sites of glucose disposal. KD is a well-defined approach to induce weight loss, with its role in muscle adaptation and muscle hypertrophy less understood. Considering this lack of knowledge, the aim of this review was to examine the scientific evidence about the effects of KD on muscle hypertrophy. We first described the mechanisms of muscle hypertrophy per se, and secondly, we discussed the characteristics and the metabolic function of KD. Ultimately, we provided the potential mechanism that could explain the influence of KD on skeletal muscle hypertrophy.